Personal Attributes of Pharmacy Graduates From an Indonesian University as Care Providers - Ernawati, D.; Lee, Y.; Sunderland, B.; Hughes, Jeff (2017)
Objective: Pharmacists’ roles in providing patient care remain limited in Indonesia, hence this study aimed to determine the preparedness of pharmacy graduates from one university in Indonesia to deliver patient care. Methods: Pharmacy graduates (both registered pharmacists [104] and recent graduates eligible for registration [45]) were sent a validated self-administered survey. The survey sought their perceptions about whether they had acquired 16 patient care related attributes. Further, it sought their opinion on the desirability of having those attributes. Data were analysed using SPSS version 22.0. Results: Sixteen of 104 (15.4%) registered pharmacists and 40 of 45 (88.9%) recent pharmacy graduates participated in the study. More than 50% of participants in both groups were female and most participants were aged in their 20s. Of the recent pharmacy graduates the majority perceived they had at least partially acquired four of 16 list attributes. Male and female recent graduates had significantly different beliefs about their leadership ability (p=0.004). In comparison, most registered pharmacists perceived they had 10 out of the 16 listed attributes. Conclusion: The findings of this study suggested that pharmacy graduates should be better prepared to deliver patient care, and that curriculum redesign with expansion of experiential learnings required.